2020
DOI: 10.3389/fpls.2020.01231
|View full text |Cite
|
Sign up to set email alerts
|

Fertile Tetraploids: New Resources for Future Rice Breeding?

Abstract: Ploidy manipulation is an efficient technique for the development of novel phenotypes in plant breeding. However, in rice (Oryza sativa L.), severe seed sterility has been considered a barrier preventing cultivation of autotetraploids since the 1930s. Recently, a series of studies identified two fertile autotetraploids, identified herein as the PMeS (Polyploid Meiosis Stability) and Neo-Tetraploid lines. Here, we summarize their characteristics, focusing on the recovery of seed fertility, and discuss potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
(96 reference statements)
0
28
0
Order By: Relevance
“…Polyploids showed stronger short-term adaptive potential during environmental change due to changes in gene expression and increased genetic diversity [ 3 , 4 , 5 ]. Autotetraploid rice was derived from diploid rice by chromosome doubling through colchicine treatment to enrich the breeding germplasm of rice, which showed great biological advantages, stress resistance and high heterosis [ 6 , 7 , 8 , 9 , 10 ]. However, low seed set is a major obstacle in the utilization of autotetraploid rice at commercial level [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyploids showed stronger short-term adaptive potential during environmental change due to changes in gene expression and increased genetic diversity [ 3 , 4 , 5 ]. Autotetraploid rice was derived from diploid rice by chromosome doubling through colchicine treatment to enrich the breeding germplasm of rice, which showed great biological advantages, stress resistance and high heterosis [ 6 , 7 , 8 , 9 , 10 ]. However, low seed set is a major obstacle in the utilization of autotetraploid rice at commercial level [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the autotetraploid rice is a rich germplasm resource, but hybrid sterility has been the limiting factor for their application in hybrid rice breeding. Recently, some studies have analyzed the important contribution of meiosis-related genes ( OsMND1 ) toward increased performance of autotetraploid rice hybrids ( Xiong et al, 2019 ; Koide et al, 2020 ). In addition, it has been recently identified that polyploidy (autotetraploid and neo-tetraploid) rice hybrids exhibited higher expressions of several genes involved in carbohydrate and lipid metabolism during pollen development and displayed higher seed setting and positive heterosis as compare to parental lines ( Chen et al, 2019 ; Ghaleb et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The high-quality genome sequencing and genomic variation data provided a way to precisely resolve the population structure of plants, which also facilitated the detection of functional genes in rice (Wang et al 2018b), maize (Lai et al 2010), soybean (Lam et al 2011) and cotton (Ma et al 2018). NTRs are important fertile materials for tetraploid rice breeding, and the development of NTRs provided rice breeders a new direction for the improvement and commercial utilization of tetraploid rice (Guo et al 2017;Koide et al 2020;Ghaleb et al 2020). Understanding the genetic variations of NTRs will largely facilitate their utilization and gene functional analysis.…”
Section: Construction Of the First Large Scale Genomic Variation Repomentioning
confidence: 99%
“…After many years of tremendous efforts, a newly developed tetraploid rice with high fertility, i.e. neo-tetraploid rice, was developed by our research group through crossing of autotetraploid rice (Guo and Liu 2014;Guo et al 2016;Guo et al 2017;Bei et al 2019;Yu et al 2020;Ghaleb et al 2020), which may become new useful resources for rice breeding (Koide et al 2020). Compared with ATR, several agronomic traits improved significantly in NTR, such as seed setting and grain number per panicle, and also contained non-parental variant genes associated with fertility and yield (Yu et al 2020).…”
Section: Introductionmentioning
confidence: 99%